Responder
To solve the equation \( x^2 + 6x + 5 = 0 \) by completing the square, follow these steps:
1. Move the constant term: \( x^2 + 6x = -5 \).
2. Find half of 6, which is 3, and square it to get 9.
3. Add 9 to both sides: \( x^2 + 6x + 9 = 4 \).
4. Write as a perfect square: \( (x + 3)^2 = 4 \).
5. Take the square root of both sides: \( x + 3 = \pm 2 \).
6. Solve for \( x \): \( x = -1 \) or \( x = -5 \).
So, the solutions are \( x = -1 \) and \( x = -5 \).
Solución
Certainly! Completing the square is a useful method for solving quadratic equations of the form:
\[ ax^2 + bx + c = 0 \]
Let's walk through the process step-by-step with a specific example. Suppose we want to solve the quadratic equation:
\[ x^2 + 6x + 5 = 0 \]
**Step 1: Move the Constant Term to the Other Side**
First, subtract the constant term from both sides to set up the equation for completing the square.
\[ x^2 + 6x = -5 \]
**Step 2: Complete the Square**
To complete the square, take half of the coefficient of \( x \), square it, and add it to both sides of the equation.
1. **Find half of the coefficient of \( x \):**
\[ \frac{6}{2} = 3 \]
2. **Square this value:**
\[ 3^2 = 9 \]
3. **Add this square to both sides:**
\[ x^2 + 6x + 9 = -5 + 9 \]
**Step 3: Simplify Both Sides**
Now, simplify both sides of the equation.
\[ x^2 + 6x + 9 = 4 \]
The left side of the equation is now a perfect square trinomial.
**Step 4: Write the Perfect Square Trinomial as a Binomial Squared**
\[ (x + 3)^2 = 4 \]
**Step 5: Solve for \( x \)**
Take the square root of both sides to solve for \( x \).
\[ x + 3 = \pm \sqrt{4} \]
\[ x + 3 = \pm 2 \]
Now, isolate \( x \):
1. **First solution:**
\[ x + 3 = 2 \]
\[ x = 2 - 3 \]
\[ x = -1 \]
2. **Second solution:**
\[ x + 3 = -2 \]
\[ x = -2 - 3 \]
\[ x = -5 \]
**Step 6: Write the Solutions**
The solutions to the equation \( x^2 + 6x + 5 = 0 \) are:
\[ x = -1 \quad \text{and} \quad x = -5 \]
**Verification**
To ensure that these solutions are correct, substitute them back into the original equation.
1. **For \( x = -1 \):**
\[
(-1)^2 + 6(-1) + 5 = 1 - 6 + 5 = 0
\]
2. **For \( x = -5 \):**
\[
(-5)^2 + 6(-5) + 5 = 25 - 30 + 5 = 0
\]
Both solutions satisfy the original equation.
---
**General Steps to Complete the Square:**
If you have a general quadratic equation:
\[ ax^2 + bx + c = 0 \]
Follow these steps:
1. **Ensure the coefficient of \( x^2 \) is 1.** If not, divide the entire equation by \( a \).
2. **Move the constant term to the other side of the equation.**
3. **Take half of the coefficient of \( x \), square it, and add it to both sides.**
4. **Rewrite the left side as a perfect square trinomial.**
5. **Take the square root of both sides.**
6. **Solve for \( x \).**
This method not only helps in solving quadratic equations but also in understanding the properties of parabolas and the derivation of the quadratic formula.
Revisado y aprobado por el equipo de tutoría de UpStudy
Explicar
Simplifique esta solución